The Role of Quality Performance Metrics on Improving Procurement Effectiveness: A Case of Higher Education Students’ Loans Board, Tanzania - Getrude John Danieli; Justus Justard Justinian (International Journal of Business, Economics, and Social Development, 2026)
Procurement effectiveness for public sector is triggered by the fact that, performance measurements determine the extent of improvement in relation to the outputs and the efforts made. The government has made number of efforts in public procurement management however, there are still challenges related to poor quality in the implementation of the procurement processes. This study assessed the role of quality performance metrics for procurement effectiveness in HESLB. The specific objectives were identifying the role of compliance rate on improving quality and determining the influence of supplier defect rate on improving quality. The findings were analyzed using descriptive statistics and thematic techniques. The study variables; regulatory compliance, contract management compliance, transparency and documentation as well as staff training on compliance were significant indicators representing the role of compliance rate on quality performance improvement. Conformance to specifications, testing and inspection, information flow, and vendor rating were recognized as significant in verifying supplier defect rate on quality improvement. The study concluded that quality performance metrics ensures transparency and accountability, mitigate and reduce procurement risks, enhance regulatory and contractual compliances, smoothens record keeping and traceability, build trust, supplier relationship management, as well as minimizing the unnecessary reworking costs.